STATE AND THE LIBERALIZATION OF THE BRAZILIAN ECONOMY - Longo, Carlos Alberto (2009)
This paper argues that the last stabilization plan that succeded in Brazil coincided with the institutional reforms which took place in 1964/65 under the Castello Branco administration. These changes gave way to a decade of high economic growth that ended abruptely. Errors of policy decision in 1979/80 and later during the Sarney administration, paved the way to the stagflation of the eighties. Strutural macro disiquilibrium resulted in the erosion of public revenues and large debt arrears which compromised the efficacy of monetary and fiscal policies. Many attempts to stabilize the price level and change institutions during the Collor administration failed due to inconsistent policy targets and lack of a well designed development plan. Not matched by permanent fiscal adjustments and major structual reforms the observed advances in the liberalization, privatization, and deregulation programs may be aborted and lead to wasteful disindustrialization.